2018
DOI: 10.1021/acs.chemmater.8b00305
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous H2 Desorption Rate of NaAlH4 Confined in Nitrogen-Doped Nanoporous Carbon Frameworks

Abstract: Confining NaAlH4 in nanoporous carbon scaffolds is known to alter the sorption kinetics and/or pathways of the characteristic bulk hydride reactions through interaction with the framework at the interface, increased specific surface area of the resulting nanoparticles, decreased hydrogen diffusion distances, and prevention of phase segregation. Although the nanosize effects have been well studied, the influence of the carbon scaffold surface chemistry remains unclear. Here we compare the hydrogen sorption char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 42 publications
0
55
0
Order By: Relevance
“…The effects of doping a C-matrix with heteroatoms are scarcely studied so far. Carr et al presented how N-doping affects NaAlH 4 [136], while we exposed the impact of this element over LiBH 4 [133]. This N-doped material was decorated with metallic nanoparticles (Ni, Co, and their mixtures).…”
Section: Matrixmentioning
confidence: 99%
“…The effects of doping a C-matrix with heteroatoms are scarcely studied so far. Carr et al presented how N-doping affects NaAlH 4 [136], while we exposed the impact of this element over LiBH 4 [133]. This N-doped material was decorated with metallic nanoparticles (Ni, Co, and their mixtures).…”
Section: Matrixmentioning
confidence: 99%
“…For instance, the heteroatom hybrid carbon scaffold apparently alters the hydrogen desorption properties of the confined NaAlH 4 . The dehydrogenation activation energies are 44 and 75 kJ mol −1 , respectively, for NaAlH 4 confined in nanopores carbon with/without nitrogen‐doping (Figure b) . Embedding catalytic additive into nano‐porous media would create a synergetic effect on NaAlH 4 .…”
Section: Hydrogen Storagementioning
confidence: 99%
“…b) Schematic illustration of the influence of the carbon scaffold surface chemistry on the dehydrogenation of NaAlH 4 . Reproduced with permission . Copyright 2018, American Chemical Society.…”
Section: Hydrogen Storagementioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the dehydrogenated sample could be rehydrogenated at 120°C under 101 bar hydrogen pressure, demonstrating excellent reversibility and stability. Recently, Carr et al [212] reported that NaAlH 4 melt infiltrated into nitrogen-doped nanoporous carbon frameworks exhibited a lowered E a value for dehydrogenation by 70 kJ mol −1…”
Section: Nanoscalingmentioning
confidence: 99%